MODEL PENGHIJAUAN DANAU SRI BANDAR KAYANGAN, KECAMATAN RUMBAI PESISIR KOTA PEKANBARU (Jurnal Kajian Lingkungan, 2014)
This study aims to identify the potential of natural resources and analyze models of ecotourism in the greening of development Bandar Sri Kayangan Lake Shore Tassel. This research has been carried out on 3 May to 27 June 2013. Survey method qualitatively analyzed descriptively. Primary data were collected through field observation, interviews and questionnaires survey with SWOT analysis. Found 54 species of vegetation. Types of plants suitable for greening are angsana (Pterocarpus indicus), trembesi (Albizia saman), rambutan hutan (Naphelium sp.), manggis (Garcinia sp.), Mendarahan (Myristica sp.), karet (Hevea brasilensis), bamboo (Family: Poacea), ara-ara (Ficus sp.), sukun (Artocarpus sp.), applicability (Artocarpus sp.), cempedak (Artocarpus integer), nangka (Artocarpus heterophyllus), rengas (Gluta sp.), and banyan (Ficus Benyamina). Communitiesâ participation (government and other stakeholders) in the development of ecotourism is low. Need an integrated inter-agency coordination among local governments so that the implementation can be well integrated in accordance with spatial planning and RDTR and can have a clear policy and a firm local regulations governing the implementation of the program.Keywords: Ecotourism, Greening